SISTEM PENDUKUNG KEPUTUSAN REKOMENDASI HOMESTAY DI KOTA PAGAR ALAM DENGAN METODE TOPSIS - Masdalipa, Risnaini; Setiadi, Dedi; Syahri, Riduan ((JITEK)Jurnal Ilmiah Teknosains, 2023)
Technological developments can be used appropriately and properly will provide benefits and facilitate human work. The decision support system is an information system that can be used to assist in decision making, in this case, namely providing homestay recommendations to tourists who will visit the city of Pagar Alam which is a tourist destination in South Sumatra. Tourists who will stay at homestays must come directly to several homestays to ask about the rental price and facilities provided by the homestay manager. Sometimes people who are looking for a homestay don't immediately match the homestay they are visiting, so they have to find another homestay that is suitable and in accordance with the available budget so that this situation is not optimal, because the process for people to find a suitable homestay can take a long time. The method used is Technique for Order of Preference by Similiarty to Ideal Solution, which is a method for solving Multi Attribute Decision Making problems. The system development uses the Rapid Application Development (RAD) method, which is a process model used in incremental software development, especially for short processing times, which consists of three stages, namely requirements planning, design workshop, implementation. From the calculation results of the TOPSIS method with four criteria determined for several alternatives, according to the selection of criteria by the user, as well as the results of ranking alternatives with the highest preference value, namely 0.5962, and kia homestay as a recommendation according to what is expected by the user.